Application of Project-Based Learning in Islamic Education using the Scientific Approach - Jauhari, Yan Yan Al; Thelma, Chanda Chansa (Al-Qalam Institue, 2023)
Education is one of the basic needs of humans as cultured and rational beings who also act as caliphs on earth. Islamic Religious Education (PAI) functions to form humans who are faithful, pious, have noble character, and have a complete personality through the transfer of experience, knowledge, and skills. This study aims to examine the application of a scientific approach in PAI learning with the Project Based Learning (PBL) method in high schools. This study uses a descriptive field research method with a qualitative approach. Data were collected through observation, interviews, and documentation of PAI teachers and the learning process. The analysis was carried out inductively to understand the existing phenomena. The results of the study showed that PAI teachers designed a scientific approach before the semester began by reviewing the syllabus, Core Competencies (KI), Basic Competencies (KD), educational calendar, materials, methods, learning models, assessments, time allocation, and learning resources. The application of a scientific approach with the PBL method involves learning activities including preliminary, core, and closing activities. This approach makes students more active in the learning process, especially in the 5M stages: observing, asking, trying, reasoning, and communicating. The contribution of this research lies in the finding that a scientific approach applied with PBL strategies can increase student motivation and engagement, thereby creating a more meaningful learning experience according to each student's learning style.